Quantitative and Semiquantitative Health Risk Assessment of Occupational Exposure to Styrene in a Petrochemical Industry - Vahid Ahmadi Moshiran; Ali Karimi; Farideh Golbabaei; Mohsen Sadeghi Yarandi; Ali Asghar Sajedian; Aysa Ghasemi Koozekonan (Elsevier, 2021)
Background: Styrene is one of the aromatic compounds used in acetonitrile-butadiene-styrene (ABS) producing petrochemicals, which has an impact on health of workers. Therefore, this study aimed to investigate the health risks of styrene emitted from the petrochemical industry in Iran. Methods: Air samples were collected based on NIOSH 1501 method. The samples were analyzed by the Varian-cp3800 gas chromatograph. Finally, risk levels of styrene's health effects on employees were assessed by the quantitative method of the U.S. Environmental Protection Agency (U.S. EPA) and the semiquantitative way by the Singapore Occupational Safety and Health Association. Results: Based on the results, the employees had the highest average exposure to styrene vapors (4.06×10−1mg.(kg−day)−1) in the polybutadiene latex (PBL) unit. Therefore, the most top predictors of cancer and non-cancer risk were 2.3×10−4 and 7.26×10−1, respectively. Given that the lowest average exposure (1.5×10−2mg.(kg−day)−1) was in the dryer unit, the prediction showed a moderate risk of cancer (0.8×10−6) and non-cancer (2.3×10−3) for the employees. The EPA method also predicted that there would be a definite cancer risk in 16% and a probable risk in 76% of exposures. However, according to the semiquantitative approach, the rate of risk was at the "low" level for all staff. The results showed that there was a significant difference (p < 0.05) between the units in exposure and health risk of styrene (p < 0.05). Conclusion: Given the high risk of styrene's health effects, appropriate control measures are required to reduce the exposure level.